Can we distinguish conventional osteosarcoma subtypes (osteoblastic and chondroblastic) based on their magnetic resonance signal intensities? - Gülçin Bozbeyoğlu Sabriye; Yildirim Ayse Nur Toksoz (Srpski Arhiv za Celokupno Lekarstvo, 2023)
Introduction/Objectives. Osteosarcoma is the most common primary malignant bone tumor in adolescents and young adults, with a tendency to produce variable amounts of osteoid, cartilage, and fibrous matrices. The objective of this study is to differentiate between osteosarcoma subtypes: osteoblastic and chondroblastic according to their magnetic resonance imaging (MRI) signal intensities and X-ray findings. Methods. We performed a retrospective analysis for 21 pathologically proven osteosarcoma subtypes: osteoblastic (n = 14) and chondroblastic (n = 7). Conventional images of the bone of origin, periosteal reactions, lytic and sclerotic features, the presence of calcification, and pathological fractures were investigated with X-rays. We measured the mean region of interest values for each lesion with MRI sequences. Results. Among the osteosarcoma lesions, 57% were localized at the knee. X-ray evaluations of the osteoblastic osteosarcomas revealed pure lytic lesions in 35.7%, and pure sclerotic lesions in 42.9% cases. Chondroblastic osteosarcomas revealed pure lytic lesions in 14.3% and pure sclerotic lesions in 42.9% cases. Due to variable osteoblastic, chondroblastic, and fibroblastic areas and proportions of the ossified matrix, osteosarcoma lesions have a heterogeneous MRI signal. However, no statistically significant value was detected. Conclusion. According to our results, MRI signal characteristics and X-ray findings may not be able to distinguish osteosarcoma subtypes, so prospective studies with larger patient cohorts are needed.